Analisis Pendapatan Usahatani dan Pengolahan Tanaman Nilam di Desa Tompasobaru Dua Kecamatan Tompasobaru Kabupaten Minahasa Selatan - Onibala, Semuel Alfa Yeheskiel; Memah, Melsje Yellie; Benu, Noortje Marsellanie (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze the farming and processing income of patchouli plants in Tompasobaru Dua Village, Tompasobaru District, South Minahasa Regency. The research was conducted from May to July 2024 with data collection methods through direct interviews with patchouli farmers. Data analysis included the calculation of production costs, revenue, net income, and R/C ratio to assess economic efficiency. The results showed that the total net income of patchouli farming and processing per one harvest period (6 months) reached Rp923,342,751, with an average of Rp76,945,229 per farmer. Total production costs incurred by farmers amounted to Rp442,957,249 (an average of Rp36,913,104 per farmer), while total revenue reached Rp1,366,300,000 (an average of Rp113,858,333 per farmer). The R/C ratio value of 3 indicates that patchouli farming in the research location is economically feasible and profitable.